α-ketoglutarate (αKG) acts as a protective factor against chronic stress and has antidepressant properties by modulating BDNF levels in the brain - Eid, Fady (2022)
Major depression and anxiety are one of the most common mental disorders worldwide. Attempts to alleviate these mental burdens are usually through psycho-therapeutic approaches, but little focus has been placed on lifestyle modifications. Adoption of these modifications, such as physical exercise, improved dietary intake, and proper sleep, have served as a nexus between clinical treatments as well as general health promotion. A multitude of studies points to how physical exercise has positive outcomes on depression and anxiety via the induction of a neurotrophic factor known as brain-derived neurotrophic factor (BDNF). α-ketoglutarate (aKG) was recently identified as a factor that is released into the blood upon exercise. In this study, we investigated whether aKG has prophylactic and antidepressant effects in chronic social defeat stress and chronic variable stress models of depression, as well as unravel the underlying molecular mechanisms. Our work shows that aKG serves as a potential prophylactic treatment for depression in both males and females through the modulation of BDNF in specific brain regions. In males, aKG pretreatment promotes resilience to stress via the PGC1a-BDNF axis within the hippocampus. Moreover, aKG exhibited antidepressant effects in susceptible female mice by modulating BDNF levels. In the hippocampus, aKG increases BDNF levels possibly through the PGC1a-BDNF pathway. In the NAc, aKG decreases BDNF levels possibly through the FNDC5-BDNF pathway.